Nonlinear Optics with Coupled Twin-Microresonators - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Yan, Haochen; Zhang, Hao; Bi, Toby; Alabbadi, Abdullah; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
Linear and nonlinear light interactions in coupled microresonators are investigated. In our experiments, we can tune the coupling gap between two resonators to investigate symmetry breaking of hybridized counterpropagating modes.
CRIS-Team Scopus Importer:2025-04-01